2013
DOI: 10.6000/1929-4409.2013.02.47
|View full text |Cite
|
Sign up to set email alerts
|

‘Notes on a Scandal’: Why do Females Engage in Abuse of Trust Behaviours?

Abstract: Although an evident reality in organisations where females work with young people, there has been no specific research to date exploring why females in positions of trust engage in sexually abusive relationships with adolescents. This study investigated the subject through a qualitative analysis of ten case studies from England drawn from the employment and safeguarding environment, comparing findings with existing studies into female sexual offenders in general, research into male 'professional perpetrators '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…She also found the women used similar grooming methods to other educators and were high achievers in their careers. Darling's (2013) case study of ten UK women who had committed 'abuse of trust' sexual offences against 16 and 17 year olds in their professional care, found that the women had similar aetiological factors identified in general female sex offender populations, including unstable lifestyles, relationship difficulties, low self-esteem and emotional self-management problems. Differences were identified in lower levels of substance abuse, a higher age range and socio-economic status and less social skills deficits and chaotic and abusive backgrounds in the sample group.…”
Section: Female-perpetrated Csa In Organisationsmentioning
confidence: 96%
See 1 more Smart Citation
“…She also found the women used similar grooming methods to other educators and were high achievers in their careers. Darling's (2013) case study of ten UK women who had committed 'abuse of trust' sexual offences against 16 and 17 year olds in their professional care, found that the women had similar aetiological factors identified in general female sex offender populations, including unstable lifestyles, relationship difficulties, low self-esteem and emotional self-management problems. Differences were identified in lower levels of substance abuse, a higher age range and socio-economic status and less social skills deficits and chaotic and abusive backgrounds in the sample group.…”
Section: Female-perpetrated Csa In Organisationsmentioning
confidence: 96%
“…There have been several literature reviews and comment pieces about female teachers (Knoll, 2010;Solis & Bendeker, 2012;Stennis, 2006) but very little empirical research. With the exception of the few studies exploring organisational sexual abuse or educator sexual misconduct which have included small numbers of females within their samples (Erooga et al, 2012;Faller, 1987;Finkelhor, Burns, Williams & Kalinowski, 1988;Jaffe, Straatman, Harris, Georges, Vink, Reif, 2013;Ratliff & Watson, 2014;Williams & Farnell, 1990); Hunt's (2006) research in Australia; a US case study on female teachers who sexually offend against students (Stranger, 2015); and a UK study into women who engaged in sexual abuse of 16 and 17 year olds in their professional care (Darling, 2013;Darling & Antonopoulos, 2013), the authors have found no other recent published empirical studies exploring this phenomenon specifically. Consequently, researchers have called for more research into this field (Bunting, 2005;Hunt, 2006;Sullivan & Beech, 2002.…”
Section: Female-perpetrated Csa In Organisationsmentioning
confidence: 99%
“…It was particularly evident that more female teachers continued with their abusive behaviour after it had been discovered than their male counterparts. This could potentially be the result of the extent of female perpetrator's emotional attachment and investment in the abusive relationship found in other studies (Darling & Antonopoulos, 2013;Darling, 2018) where some women have been particularly reluctant to give up what they perceive to be a genuine and lasting, equal relationship and have been prepared to give up their homes, families, and careers in order not to do so. Such circumstances suggest that there should be close monitoring of both perpetrator and victim behaviour after sexual misconduct has been identified, including during any employment suspension period and police or professional regulator investigations.…”
Section: Discussion and Implications For Policy And Practicementioning
confidence: 95%
“…This highlights the importance of understanding situational, environmental and contextual factors in addressing opportunities for CSA in organisations. While some existing research indicates that abusers with a specific sexual interest in children use organisations as a way to access and perpetrate abuse (Faller, 1987;Sullivan & Beech, 2002), other studies have found less evidence of known predisposition or motivation to abuse prior to working in organisational contexts (Darling & Antonopoulos, 2013;Erooga et al, 2012aErooga et al, , 2012Finkelhor et al, 1988). Given the view that it is probably much more common for abuse-related motivations and behaviours to arise within the course of the individual's involvement in the child or youth-serving setting (Erooga et al, 2012;Finkelhor et al, 1988;Smallbone & McKillop, 2016;Smallbone & Wortley, 2000) then the situational and contextual factors related to the relationships between adults and children in organisations become increasingly important.…”
Section: Organisational Csamentioning
confidence: 99%
“…Recent years have seen unprecedented public and political attention directed towards organisational child abuse and child sexual abuse (CSA), and in particular it has been the focus of increasing numbers of national inquiries and local investigations. However, despite growing research into the issue, significant gaps still remain in the literature (McNeish & Scott, 2018) and until recently there has been very little empirical research conducted examining females who sexually offend in organisations (Darling 2018;Darling & Antonopoulos, 2013;Darling, Hackett & Jamie, 2018). This is problematic for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%